Integrating Resilience Attributes into Operations : A Note for Practitioners - Ospina, Angelica V. (Washington, DC : World Bank, 2022)
Since 2015 the Africa Climate Business Plan (ACBP) has been a galvanizing platform for climate action. Progress achieved to date includes resilience capacity enhancement across the ACBP portfolio, demonstrating that well-designed interventions can further bolster multiple pathways to build resilience. The Africa Climate-Resilient Investment Facility (AFRI-RES) aims to strengthen the capacity of African institutions and the private sector to plan, design and implement investments in selected sectors to increase their resilience to climate change. One AFRI-RES’ components is the identification of good practices and the development of guidelines to inform decision-making on incorporating climate risk into infrastructure planning and design, across different sectors and stages of the project cycle. The Resilience Attributes Guidance Note builds on the results of an ex-post analysis conducted on 57 ACPB projects, which indicates that core resilience capacities could be built through multiple pathways by paying attention to activities that strengthen resilience attributes (i.e. robustness, learning, redundancy, rapidity, connectedness, diversity, flexibility and inclusion). These attributes can be realized through a variety of activities or interventions designed into a project, and contribute to building adaptive, absorptive, and/or transformative capacities. This approach was further been validated through meetings with Task Teams from the Africa Region, where teams expressed a strong interest to explore further the viability of testing and applying this approach in an ex-ante context. This Guidance Note presents a dynamic approach that can be adapted by TTLs to meet their specific needs and improve the design and implementation of resilience building operations. Instead of a prescriptive or an exclusive approach, the Guidance provides multiple entry points for teams to complement, deepen and/or strengthen the way they think about, design, implement and track progress of resilience initiatives.